Effectiveness Of Ursodeoxycholic Acid In The Management Of Symptomatic Gallstone Disease: A Cross Sectional Study - Raj, Hans; kumar, Mahendra (Journal of Neonatal Surgery, 2025)
Background: Gallstone disease is a frequently encountered hepatobiliary condition that commonly presents with biliary colic and dyspeptic complaints. Ursodeoxycholic acid (UDCA) has emerged as a conservative therapeutic option for selected patients with cholesterol gallstones; however, evidence regarding its effectiveness in symptomatic cases from routine clinical practice remains limited. Objective: To assess the effectiveness of Ursodeoxycholic acid in alleviating symptoms and reducing gallstone burden in patients with symptomatic gallstone disease. Methods: This cross-sectional study included patients diagnosed with symptomatic gallstone disease who were treated with Ursodeoxycholic acid. Clinical symptoms, ultrasonographic findings, and treatment outcomes were evaluated and analyzed statistically. Results: A significant reduction in pain and dyspeptic symptoms was observed following therapy. Ultrasonographic follow-up revealed partial or complete dissolution of gallstones in a proportion of patients, particularly those with smaller cholesterol stones. Conclusion: Ursodeoxycholic acid represents an effective and non-invasive treatment modality for symptom control and gallstone reduction in carefully selected patients with symptomatic gallstone disease.